Corruption and social rights accountability - Annika Engelbert; Markus Kaltenborn (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2019)
Transnational criminal law treaties traditionally dominate the international anticorruption regime; yet, corruption has not considerably decreased since their coming into force. It therefore seems appropriate to broaden the legal perspective: Corruption as a threat to welfare, safety, and physical integrity of the individual can be conceptualized as a human rights violation. This paper argues that it is possible indeed to establish causal links between the misallocation of public funds, including budget distortions and underfunding of anti-corruption institutions, and a structural infringement of social human rights. We present several human rights instruments suitable to combat corruption with regard to social rights realization. In particular, we assess the capacity of public interest litigation, as well as related contextual legal and political conditions for the case of Kenya. With its new Bill of Rights, Kenya has great potential to spearhead a progressive impact litigation strategy targeting corruption-induced social rights infringements.
Keywords: 330